2007
DOI: 10.1007/s00299-007-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

Sample topography and position within plant body influence the detection of the intensity of green fluorescent protein fluorescence in the leaves of transgenic tobacco plants

Abstract: The effect of the type of leaf tissue selected for the study of green fluorescent protein (GFP) fluorescence intensity was investigated here using the T(1) generation of transgenic tobacco expressing the m-gfp5-ER gene. The fluorescence of GFP was detected by fluorescence binocular microscope coupled with the CCD camera and quantified by means of image analyses using the Lucia((R)) software. Mean brightness values from various leaf tissues were compared. First, an original data revealing the significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…An arrow indicated position of the product of expected mass. The polymerase chain reaction (PCR) following the procedure described by Hraška et al (2008) was used to confirm the presence of the gfp transgene in regenerated shoots and to exclude the simultaneous occurrence of the vir gene as a consequence of persistance of the vector bacteria after 6-9 months to SAAT. MW = 100 bp molecular weight marker; PC = positive control (pBINmGFP5-ER plasmid); 0-150 = DNA isolated of double-selected flax plants regenerated from transformation experiments based on a simple co-cultivation (0) or sonication for 50-150 s (50-150) preceeding to the co-cultivation; NC = negative control (DNA from untransformed plants) 50 s of sonication (35 kHz, 35 W) could substantially increase the efficiency of stable flax transformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An arrow indicated position of the product of expected mass. The polymerase chain reaction (PCR) following the procedure described by Hraška et al (2008) was used to confirm the presence of the gfp transgene in regenerated shoots and to exclude the simultaneous occurrence of the vir gene as a consequence of persistance of the vector bacteria after 6-9 months to SAAT. MW = 100 bp molecular weight marker; PC = positive control (pBINmGFP5-ER plasmid); 0-150 = DNA isolated of double-selected flax plants regenerated from transformation experiments based on a simple co-cultivation (0) or sonication for 50-150 s (50-150) preceeding to the co-cultivation; NC = negative control (DNA from untransformed plants) 50 s of sonication (35 kHz, 35 W) could substantially increase the efficiency of stable flax transformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GFP was monitored continuously up to 30 days following the SAAT with the aim of evaluating and selecting stable transformed tissues and plants. After a six to nine months period the polymerase chain reaction (PCR) following the procedure described by Hraška et al (2008) was used to confirm the presence of the gfp transgene in regenerated shoots and to exclude the simultaneous occurrence of the vir gene as a consequence of persistance of the vector bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, untransformed plant tissues were used as negative controls for adjusting the parameters to ensure the absence of GFP fluorescence in nontransformed leaves. Secondly, it has been reported that expression of the marker gene is influenced by differences in leaf tissue, leaf developmental stage, and location within the plant body (Hraska et al 2008). Different cytoplasmic density of cells in young and older leaves leads to the ''dilution'' of GFP in older tissues thereby weakening the fluorescence (Omar and Grosser 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the green channel counts observed in negative controls should be subtracted from the counts observed in GFP-expressing plants. Developmental age (Harper and Stewart 2000; Halfhill et al 2003; Hraška et al 2006, 2008), environmental growth conditions (Halfhill et al 2004) and plant species (Zhou et al 2005) can affect the efficiency of GFP fluorescence detection. Thus, controls should be physiologically identical to GFP-expressing plants in terms of genetic background, developmental ages and growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving direct comparison of surface fluorescence and GFP content in soluble protein extracts have shown linear relationships (Blumenthal et al 1999; Harper et al 1999; Richards et al 2003; Halfhill et al 2004). Green fluorescent protein leaf surface fluorescence can be measured with probes that clip onto leaves, laboratory-based fluorescent imaging systems (Niwa et al 1999; Millwood et al 2003; Richards et al 2003; Halfhill et al 2004; Stewart 2006) and dissecting fluorescent microscopes (Zhou et al 2005; Jach 2006; Hraška et al 2008; Yambao et al 2008). Although all of these systems have specific advantages (Halfhill et al 2004), they are all expensive.…”
Section: Introductionmentioning
confidence: 99%